Youth’s Perceptions in Wearing Colored Contact Lens - Farid Yusuf (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2020)
Colored contact lens is one of the trend that most youth have been following these days. Not only for medical and optical purpose, colored contact lens can be used for cosmetic. People can buy colored contact lens either online or offline. However, most youth do not know that they need to consult their condition with RO in optic. They rely their trust on the internet and set aside the significant variable in wearing colored contact lens. This research use phenomenology as the research approach by doing interviews and observation in two different locations (Kacamata Anca and Optik Melawai TP Surabaya). The researcher found that either youth that purchase colored contact lens online or offline shows different characteristics. The higher youth’s age, education, economy, and experience, the better youth’s characteristic regarding colored contact lens. Older youth will have higher education and higher education have bigger opportunities to have a better job. Better job makes higher income. People that economically stable will have more time to think about their health condition rather than people with lower income that more focus on their daily needs. While base curve, eyes diameter, Distribution Permit, and types of contact lenses are the significant variables that most youth did not understand. Youth need to improve their knowledge before wearing colored contact lens because their characteristic is still average, so it is better fot youth to not just follow the trend but also become more discipline and critical person especially related to eyes healthiness.